Desarrollo e implementación de aplicación web para el ingreso y control de tiempos de deportistas del club de natación “Guayaquil Sporting Club” - Macías Martínez, Danisa Carolina (2023)
The swimming club "Guayaquil Sporting Club" carries out various activities, such as the registration of athletes, sale of sporting goods, internal and external competitions, among others. These activities have processes that were handled manually internally, which was difficult to cope with. The club requires a system that will facilitate internal processes related to the administration and management of athlete data.